Women's Responsibilities in Choosing Injectable Family Planning in Timor Tengah Selatan District - Rahayu, Putu Sri; Tamtomo, Didik Gunawan; Budihastuti, Uki Retno (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Injectable contraception is the most popular contraceptive method in Indonesia with a user percentage of 63.71% of the coverage of modern family planning users. In addition to the benefits and practicality of its use, this method also has various negative impacts that can endanger the health of the acceptor. This study aims to explore and describe the acceptor's response to the negative impacts experienced as a form of responsibility for the health of the acceptor. Subjects and Method: This study was conducted using descriptive qualitative method with triagulation analysis technique that connects empirical facts. The dependent variable is injectable family planning. The independent variables are responsibility, patriarchal culture, and decision making. The study was conducted on 18 informants who are injection family planning acceptors in Timor Tengah Selatan Regency. Results: The informants do not mind experiencing the negative impacts of using injectable contraceptives and prioritize the benefits and practicality of their use. The low level of education of informants is a problem in receiving and digging information. Limited access to information is also hindered by the lack of infrastructure to reach health facilities. The high pressure of patriarchal culture is one of the decision-making factors and the high number of injecting family planning users. Conclusion: The acceptor's lack of information regarding the contraceptive method used is a barrier in responding to the negative impacts experienced.